Public transportation and consumer prices: Chain stores, street vendors and mom and pop stores - Angel Espinoza E. (Banco de México, 2024)
Improving public transport infrastructure changes local market conditions. In this paper, I examine the impact of the construction and operation of "Metrobus", Mexico City's Bus Rapid Transit (BRT) system on consumer prices in chain stores, street vendors, and small family-owned (mom and pop) stores. I do so through a panel event study design. I consider the construction and operation of BRT as two different phenomena; while the former is associated to street closures, the latter reduces transportation costs. I show that only prices in mom and pop stores respond to changes in local market conditions produced by the introduction of BRT. For these businesses, construction pressures prices downwards; in contrast, operation is associated with partial price recoveries. I cannot reject a null effect in prices from chain stores or street vendors.
Keywords: L11; L92; R12; R42; 330; Public Transportation; Local Markets; Price Formation